ANALISIS KUALITAS PELAYANAN PUBLIK TERHADAP PELAYANAN KTP DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN SIDENRENG RAPPANG - Lukman; Sellang, Kamaruddin (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The objective of this study is to investigate the quality assessment of KTP services provided by the Population and Civil Registry Service of Sidenreng Rappang Regency. Using the Slovin formula, a sample of 99 individuals was taken from the study's population of 482 participants. It is a descriptive kind of research. This study employed questionnaires, literature reviews, and observation as data gathering methods. The IBM SPSS Statistics 21.0 program is used in conjunction with the data analysis method. 69% of the analysis of public service quality falls into the good category, according to the study's findings. Excellent describes 63% of the KTP service procedure. At the Sidenreng District Population and Civil Registration Service, factors affecting the quality of public services have a good/influential level of 65% in the KTP service. Empathy and tangibles, the KTP service process (printing and issuing KTPs), administration, and updating procedures are some of the factors that affect the quality of KTP services provided by the public sector. Accessibility and human resources are two factors that affect the quality of KTP services. The findings of the quality of public services in the KTP service of the Population and Civil Registration Service of Sidenreng Rappang Regency and the "Impact/Significance" analysis.